- 0,7X + 2 = 65
- 0,7X = 65 - 2
- 0,7X = 63
X = 63 : ( - 0,7 )
X = - 90
Проверка
- 0,7 * ( - 90 ) + 2 = 65
63 + 2 = 65
65 = 65
-----------------------------
2X + 5 = 2 * ( X + 1 ) + 11
2X + 5 = 2X + 2 + 11
2X + 5 ≠ 2X + 13
Нет решений
---------------------------------
3Y - ( Y - 19 ) = 2Y
3Y - Y + 19 = 2Y
2Y + 19 ≠ 29
Нет решений
----------------------------------------
6 * ( 1 + 5X ) = 5 * ( 1 + 6X )
6 + 30X ≠ 5 + 30X
Нет решений
-----------------------------------------------
0,4X + 3 = 0,2 * ( 3X + 1 ) - X
0,4X + 3 = 0,6X + 0,2 - X
0,4X + 3 = - 0,4X + 0,2
0,4X + 0,4X = 0,2 - 3
0,8X = - 2,8
X = - 2,8 : 0,8
X = - 3,5
Проверка
0,4 * ( - 3,5 ) + 3 = 0,2 * ( 3 * ( - 3,5 ) + 1 ) - ( - 3,5 )
- 1,4 + 3 = 0,2 * ( - 10,5 + 1 ) + 3,5
1,6 = 0,2 * ( - 9,5 ) + 3,5
1,6 = - 1,9 + 3,5
1,6 = 1,6